Pragmatic approaches to Latin and Ancient Greek - Denizot, Camille; Spevak, Olga (Studies in language companion series, 2017)
"Pragmatics forms nowadays an integral part of the description not only of modern languages but also of ancient languages such as Latin and Ancient Greek. This book explores various pragmatic phenomena in these two languages, which are accessible through corpora consisting of a broad range of text types. It comprises empirical synchronic studies that deal with three main topics: (i) speech acts and pragmatic markers, (ii) word order, and (iii) discourse markers and particles. The specificity of this book consists in the discussion and application of various methodological approaches. It provides new insights into the pragmatic phenomena encountered, compares, where possible, the results of the investigation of the two languages, and draws conclusions of a more general nature. The volume will be of interest to linguists working on pragmatics in general, and to scholars of Latin and Ancient Greek in particular"--